Erythropoiesis and iron metabolism in Hodgkin's disease. - Al-Ismail, S. (Nature Publishing Group, 1979)
Recently developed techniques for the investigation of iron kinetics were used to study the disturbance of iron metabolism in 19 untreated patients with Hodgkin's diseases (HD). The erythroid abnormality in newly diagnosed HD appears to be confined to those patients with systemic symptoms of weight loss, night sweats and fever, and consists of depression of marrow erythroid activity. These patients had a significnatly lower haemoglobin and serum iron concentration and a higher serum ferritin concentration, both when compared to normal subjects and to those patients with HD who lacked systemic symptoms. Ineffective erythropoiesis and red-cell destruction were not significantly increased. The present findings, confirm that HD patients with systemic symptoms have a depression of erythropoiesis, and that in these patients the marrow fails to respond to the stimulus of mild anaemia.